INTEGRASI NILAI SPIRITUAL DALAM KONTEN PEMBELAJARAN SAINS SEBAGAI UPAYA MEMBANGUN KARAKTER SISWA DARI JENJANG SEKOLAH - Henny Johan; Agus Sundaryono; Bhakti Karyadi; Umaya (Universitas Bengkulu, 2024)
The concept of science has the potential to be explored in instilling spiritual values. Competence of a good science teacher is needed to integrate science learning and inculcate spiritual values. This PPM activity aims to provide knowledge and improve the competence of science teachers in presenting science learning activities that focus on cognitive abilities as well as spiritual attitudes. Community service activities (PPM) will be carried out in the form of workshop training involving students and science teachers in Rejang Lebong Regency, Bengkulu Province. Based on the results of the questionnaire, it is known that teachers and students agree on the need for the integration of spiritual values ​​through science learning. The results of the teacher's worksheet show the teacher is able to relate the concept of science to spiritual values of the greatness of God. The teacher can describe the plan for presenting these values ​​in learning activities. Students are very enthusiastic about learning science with spiritual values ​​and students are able to give examples of various phenomena related to the concept of physics and the spiritual values ​​in it. Based on the results of the response questionnaire and working papers, it can be concluded that students and teachers are highly motivated by learning science with spiritual values. After participating in the workshop, the teacher can integrate spiritual values ​​into basic competencies in science learning. Students are able to mention spiritual values ​​in various phenomena related to scientific concepts.